2004
DOI: 10.1038/sj.gt.3302313
|View full text |Cite
|
Sign up to set email alerts
|

Comparative analysis of antisense oligonucleotide analogs for targeted DMD exon 46 skipping in muscle cells

Abstract: As small molecule drugs for Duchenne muscular dystrophy (DMD), antisense oligonucleotides (AONs) have been shown to restore the disrupted reading frame of DMD transcripts by inducing specific exon skipping. This allows the synthesis of largely functional Becker muscular dystrophy (BMD)-like dystrophins and potential conversion of severe DMD into milder BMD phenotypes. Thus far we have used 2 0 -O-methyl phosphorothioate (2OMePS) AONs. Here, we assessed the skipping efficiencies of different AON analogs contain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
96
2
1

Year Published

2004
2004
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 122 publications
(99 citation statements)
references
References 37 publications
0
96
2
1
Order By: Relevance
“…This variability has been demonstrated in 2OMeAO-induced skipping of a variety of human exons in tissue culture and in a mouse carrying the human genomic dystrophin gene. But these studies have also found that a large proportion of exons are readily skipped by the use of appropriate AO sequences (21,22).…”
Section: Discussionmentioning
confidence: 99%
“…This variability has been demonstrated in 2OMeAO-induced skipping of a variety of human exons in tissue culture and in a mouse carrying the human genomic dystrophin gene. But these studies have also found that a large proportion of exons are readily skipped by the use of appropriate AO sequences (21,22).…”
Section: Discussionmentioning
confidence: 99%
“…One strategy, based on previous results obtained in mouse dystrophin exon 23 (Graham et al, 2004), was that of designing an overlapping stepped array of 2-OMe AOs complementary to the 5Ј (donor) splice site of intron 51. The other strategies examined other potential splice motifs across exon 51, including the 3Ј (acceptor) splice site and the branch point, as well as exon-internal sequences (Aartsma-Rus et al, 2004b;Wilton et al, 2007). After initial characterization in each partner laboratory (Table 2) (Aartsma- Rus et al, 2002Rus et al, , 2005Harding et al, 2007), eight AOs, six targeting the 5Ј splice site designed in the first partner laboratory (RH) (C20 to H20; Fig.…”
Section: Exon-internal 2-ome Aos Are More Efficient Than Those Targetmentioning
confidence: 99%
“…the recent PNA-Pip series) [13,14] and, therefore, the availability of reliable, rapid in vitro screens to accelerate AO discovery would be highly advantageous. In vitro screens of AO splice correcting activity have been carried out widely using H 2 K mdx cells [18] and also using DMD patient-derived cells [19][20][21][22]; however, it has been reported that such in vitro systems work less well for neutrally charged AOs (e.g. PMO or PNA) and their derivatives [20,23], which can present transfection difficulties, and that the in vitro activity of different AO chemistries seldom correlates well with their in vivo efficacy in mdx mice.…”
Section: Introductionmentioning
confidence: 99%